Application Flows - Steven J. Davis; Brenda Samaniego de la Parra (Institute of Labor Economics (IZA), 2024)
We build and analyze a new U.S. database that links 125 million applications to job vacancies and employer-side clients on Dice.com, an online platform for jobs and workers in software design, computer systems, engineering, financial analysis, management consulting, and other occupations that require technical skills. We find, first, that posting durations are quite short, often only two or three days, with a median of seven days. Second, labor market tightness has tiny effects on posting durations. Third, job seekers display a striking propensity to target new postings, with almost half of applications flowing to openings posted in the past 48 hours. Fourth, applications per posting are much too uneven to reflect random search, even within narrow market segments and job categories. Moreover, posted offer wages play no role in explaining the deviations from a random-search benchmark. Fifth, intermediaries play a huge role on both sides of the platform: Recruitment and staffing firms account for two-thirds of all postings and attract most of the applications. We relate these and other findings to theories of labor market search.
Keywords: J6; M5; 330; worker applications; job vacancies; intermediaries; tightness; vacancy durations; non-sequential search; staffing firms; recruitment firms